Prognosis of Vital Teeth Involved in Large Cystic Lesions After a Surgical Intervention: A Longitudinal Ambidirectional Cohort Study - Khalid A. Merdad; Maha Shawky; Khalid A. Aljohani; Rawia Alghamdi; Saja Alzahrani; Omar R. Alkhattab; Abdulaziz Bakhsh (Dentistry Journal)
Background/Objectives: Large cystic lesions in the maxillofacial region present a challenge for clinicians due to their impact on the health and functionality of the involved teeth. This longitudinal, ambidirectional cohort study aimed to evaluate the prognosis of vital teeth affected by large cystic lesions following surgical intervention. Methods: Data were gathered from patients at King Abdulaziz University Dental Hospital and King Fahad General Hospital in Jeddah, Saudi Arabia, between July 2021 and August 2022. Seventeen individuals with large jawbone cysts were included in the study. Clinical and radiographic assessments were performed including sensibility testing and the function of teeth. The results indicated a linear relationship between the size of postoperative bony defects and the sensibility testing of teeth. Results: Of the 63 examined teeth, 54% did not receive endodontic treatment, 33% had pre-surgical treatment, and 12.7% had post-surgical treatment. The study revealed a high prevalence of inflammatory cysts, particularly in the maxilla. Surgical enucleation was the primary treatment modality, with few postoperative complications. Conclusions: This study highlights the necessity for standardized follow-up protocols and more extensive research to develop universal guidelines for managing large cystic lesions affecting vital teeth. Understanding the prognosis of cystic lesions is crucial for effective treatment planning and ensuring optimal patient outcomes.